Evaluating Effectiveness Of ETLE and Designing ATCS Integration For Traffic Violation Reduction In Magelang Regecy - Hafidz Nurrohman; Zahwa Octavioliena; Rizal Aprianto (Politeknik Perkeretaapian Indonesia Madiun, 2025)
Transportation as a means of public mobility in Indonesia continues to face high traffic accident rates, primarily due to violations such as speeding and red-light running. Electronic Traffic Law Enforcement (ETLE) has emerged as a technology-based law enforcement solution, but its effectiveness remains limited due to the narrow coverage of static systems. This study aims to analyze the effectiveness of ETLE and design its integration with the Area Traffic Control System (ATCS) to enhance traffic violation monitoring in Magelang Regency. The research method is census approach by collecting primary violation data from static and mobile ETLE units during March 2024–2025. Analysis results indicate a decline in violations from 17,495 cases (2020) to 4,739 cases (2023), yet the limited deployment of static ETLE at only one strategic point hinders optimal detection. Integration of ETLE-ATCS across 19 traffic light (APILL) points is proposed to expand coverage through real-time detection, automated verification, and traffic signal adjustments based on real-time data. Simulations of this integrated system demonstrate the potential for more transparent and efficient law enforcement, alongside reduced accident risks. Consequently, the proposed system integration is expected to foster safer, more orderly, and sustainable transportation in Magelang Regency.